(untitled) - Cengel, Yunus A. (New York, 2010)
Looking for something great to read? Browse our editors picks for the Best Books of the Year So Far in fiction nonfiction mysteries childrens books and much more
Truyền khối
Keywords: Nhiệt,Heat,Mass transfer,Khối lượng chuyển nhượng; Truyền tải,Transmission